2017
DOI: 10.17954/amj.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Reconstruction Options of Dog Bite Injuries

Abstract: ÖZAmaç: Bu çalışmada yedi yıllık süreçte Ankara Numune Eğitim ve Araştırma Hastanesi Plastik Cerrahi Kliniği'ne köpek ısırığı nedeniyle başvuran ve danışılan hastaların değerlendirilerek, uygun tedavi yöntemlerinin ortaya konulması amaçlanmıştır. Gereç ve Yöntemler: 2002-2013 yılları arasında acil servis ve polikliniğe başvuran toplam 84 Hasta çalışmaya dahil edildi. Olgular demografik özellikler, çevre faktörleri, mevsimsel faktörler, yaralanan anatomik bölge, yaralanma karakteristiği ve klinik seyir açısında… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
(7 reference statements)
2
4
1
Order By: Relevance
“…[ 4 , 5 , 7 ] In some studies in the literature, it has been stated that injuries are often caused by owned dogs. [ 23 , 28 ] In our study, in contrast with other studies in the literature, 65.8% (n=98) of the cases were attacked by stray dogs, which is thought to be due to the higher population of stray dogs in Türkiye. Although there is no similar study in the literature, we found that 86.6% of the dog attacks were carried out by a single dog in our study.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…[ 4 , 5 , 7 ] In some studies in the literature, it has been stated that injuries are often caused by owned dogs. [ 23 , 28 ] In our study, in contrast with other studies in the literature, 65.8% (n=98) of the cases were attacked by stray dogs, which is thought to be due to the higher population of stray dogs in Türkiye. Although there is no similar study in the literature, we found that 86.6% of the dog attacks were carried out by a single dog in our study.…”
Section: Discussioncontrasting
confidence: 98%
“…In a study conducted in Türkiye, it is stated that injuries are high in rural areas,[ 24 ] while in another study it is stated that injuries are high in the city center. [ 23 ] In our study, we found that 56.4% of the injuries were in the city center. It is stated that the number of dogs in some big cities in Türkiye even exceeds the population of some districts.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations